El Acuerdo de Basilea: Estado del Arte del SARC en Colombia (2019)
The first version of the Basel Capital Accord was signed in 1988 by representatives of Group G-10. Since then, this accord has been widely implemented around the world. There has been various amendments including market risk and, lately, in Basel II, the operative risk. In Colombia, since 2002, it is mandatory for risk management in Financial Institutions.